Author Correction: A novel insight on SARS-CoV-2 S-derived fragments in the control of the host immunity (Scientific Reports, (2023), 13, 1, (8060), 10.1038/s41598-023-29588-8) - Bastos, Thais Sibioni Berti; de Paula, André Guilherme Portela; dos Santos Luz, Rebeca Bosso; Garnique, Anali M. B.; Belo, Marco A. A.; Eto, Silas Fernandes; Fernandes, Dayanne Carla; Ferraris, Fausto Klabund; de Pontes, Leticia Gomes; França, Tábata Takahashi; Barcellos, Leonardo José Gil; Veras, Flavio P.; et al. (Springer Nature, 2023)
Correction to: Scientific Reports, published online 17 May 2023 The original version of this Article contained an error in the Introduction, where a reference has been included incorrectly as a hyperlink. The correct reference is listed below: Galindo-Villegas J. The Zebrafish Disease and Drug Screening Model: A Strong Ally Against Covid-19. Front. Pharmacol.11 (680). (2020). In the Introduction, “In addition to traditional host models, zebrafish (Danio rerio), an extremely versatile and attractive organism, have gained prominence in research.” now reads: “In addition to traditional host models, zebrafish (Danio rerio), an extremely versatile and attractive organism, have gained prominence in research20.” The reference has now been added to the Reference list as Reference 20. As a result, the subsequent references have been renumbered. The original Article has been corrected.